Cluster evolution in mature Industrial cluster. The case of Prato Marshallian ID after the entrance of Chinese firm populations (1945-2011) - Luciana Lazzeretti; Francesco Capone (European Regional Science Association (ERSA), 2014)
The aim of the present research is to participate to the recently resurged debate on cluster life cycle theory among scholars of New Evolutionary Geography and Industrial Economics, starting from the seminal contributions of Menzel and Fornhal (2010). Authors pointed out how the very cluster dynamics is both the driver for the movement of a cluster through a life cycle and the reason why this movement differs from the industry life cycle. Cluster life cycle is recently attracting increasing attention and notwithstanding some authors as Martin and Sunley (2011) showed some criticism, proposing alternative approaches, they agreed the cluster evolution literature is still in search of an appropriate analytical frame work and is necessary to follow an evolutionary approach instead of a deterministic perspective, considering also the analysis of local contexts. Boschma and Fornahl (2011) reaffirming this position, indicate a ?roadmap for future research' able to integrate different approaches and promote the production of a coherent mass of longitudinal empirical study necessary to verify theoretical hypothesis, at the moment not sufficiently adequate. The work deals with the evolution of textile-clothing Marshallian Industrial District (MID) in Prato, focusing on last twenty years, characterised by the settlement of a large numbers of Chinese firms. The Prato MID is in a transformation/decline phase due for many scholars to the entrance of Chinese immigrants as well as the recent economic crisis and the effects of globalization (Johnson et al., 2009). We contribute to this debate following an evolutionary approach according to the Organisational Ecology and density dependence (Hannan and Freeman, 1989; Hannan and Carroll, 1992). The analysis is carried out on Italian and Chinese firms in Prato MID. Data are collected elaborating the Registry of Economic Activity held by the Province of Prato (1990-2011) and integrated with a previous database constructed from REA from Chambers of Commerce of Prato and Florence (1945-1998) (Lazzeretti and Storai, 2003; Lazzeretti and Terchi, 2002). We carried out demographic analysis on the natality and mortality of firms of Prato MID and we tested ecological models in order to establish relationships between legitimation and competition ecological processes and different life cycle phases. Results allow us to reconstruct the internal dynamics of Prato MID from its birth till today and identify in which stage of the life cycle it is currently, providing a theoretical and empirical contribution to the study of cluster evolution, through the Organisational Ecology.
Keywords: R12; L67; R23; 330; Cluster evolution; cluster life cycle; organisation ecology approach; Prato; textile-clothing; Industrial District; Chinese firms population